RANCANG BANGUN E-COMMERCE PANDUKRIA BERBASIS FRAMEWORK CODEIGNITER - Muhyiddin Zainul Arifin; Hasan Bisri Isa Alfaris; Siti Sufaidah; Agus Sifaunajah (SAINTEKBU, 2019)
In Jombang district there is considerable potential if thorn pandanus is managed optimally. The community has long been a pandanus craftsman and their businesses are mostly inherited so this shows that pandanus business is the main support of the family economy. But the fact is that the Pandan Duri woven craft business has not been able to improve their lives. This is because the pandanus woven business is a side job, the products produced are less diverse and only in the manufacture of woven mats, and marketing is limited to local markets and the surrounding communities. As one of the efforts to improve the economy of the community, thorns and pandanus woven craftsmen created e-commerce software through the Knowledge-based Economy Development Program by hoping that besides being able to accelerate economic improvement, the woven craftsmen community could also become entrepreneurial development and achieve achievements. Intellectual Property Rights (IPR) in the form of patents from marketing application software products that have been made. The software application is built called PanduKRIA and its implementation uses the language of the PHP program based on CodeIgniter framework and MySQL The methodology used is to conduct a site survey to see the condition of the community in the four sub-districts as the basis of Kria SME thorn pandanus craftsmen, namely in Kudu District, Ploso District, Kabuh District, and Plandaan District. Furthermore, the market share will be strengthened so that these products can penetrate national and international markets. Market strengthening is done by synergizing thorn pandanus woven products in the PanduKria application program application based on the website. Key words: Kria Pandan Duri, Codeigniter, Webbing, E-Marketing.